2017
DOI: 10.1128/jvi.00369-17
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Nature of Human T-Cell Leukemia Virus Type 1 Particle Cores as Revealed through Characterization of a Chronically Infected Cell Line

Abstract: Human T-cell leukemia virus type 1 (HTLV-1) is the etiological agent of adult T-cell leukemia (ATL) and HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). HTLV-1 cell-to-cell transmission is dependent on the release of infectious virus particles into the virological synapse. The HTLV-1 particle structure is still poorly understood, and previous studies analyzed viruses produced by transformed lymphocytic cell lines chronically infected with HTLV-1, particularly the MT-2 cell line, which harbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 65 publications
2
14
0
Order By: Relevance
“…Although MEF-2B mRNA levels for all cell lines were comparable to Jurkat there was a clear downregulation of MEF-2B at the protein level across all cell lines. Furthermore, we also observed similar MEF-2A expression patterns in a capillary-based electrophoresis approach, where there was increased expression of MEF-2A in all cell lines except SP cells, which is an IL-2-dependent cell line that contains only one copy of the virus in its genome (44). Similarly, M8166, a lymphoblastoid cell line that harbors a defective provirus of HTLV-1 did not demonstrate increased MEF-2A expression (45).…”
Section: Discussionsupporting
confidence: 72%
“…Although MEF-2B mRNA levels for all cell lines were comparable to Jurkat there was a clear downregulation of MEF-2B at the protein level across all cell lines. Furthermore, we also observed similar MEF-2A expression patterns in a capillary-based electrophoresis approach, where there was increased expression of MEF-2A in all cell lines except SP cells, which is an IL-2-dependent cell line that contains only one copy of the virus in its genome (44). Similarly, M8166, a lymphoblastoid cell line that harbors a defective provirus of HTLV-1 did not demonstrate increased MEF-2A expression (45).…”
Section: Discussionsupporting
confidence: 72%
“…Cell-free particle infectivity for HTLV-1 is low, and recent observations have indicated that only a portion of mature HTLV-1 particles have intact cores (57). Infectious HTLV-1 spread is more heavily dependent upon cell-to-cell transmission than that of HIV-1.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is possible that the biogenesis of HTLV-1 Gag puncta by recruitment of Gag along the plasma membrane is a more efficient mode of particle production during cell-cell contacts. Cell-free particle infectivity for HTLV-1 is low, and recent observations have indicated that only a portion of mature HTLV-1 particles have intact cores ( 57 ). Infectious HTLV-1 spread is more heavily dependent upon cell-to-cell transmission than that of HIV-1.…”
Section: Discussionmentioning
confidence: 99%
“…As infection of T cells by free HTLV-1 virions is extremely inefficient (10)(11)(12), T-cell infection occurs through mechanisms involving contact between an effector cell (infected with HTLV-1) and a target cell. In the context of T-cell-to-T-cell infection, initiation and stabilization of effector cell-target cell contact is mediated by intercellular adhesion molecule 1 (ICAM-1) on the surface of the effector T cell engaging with lymphocyte functioning antigen 1 (LFA-1) on the target cell (13,14).…”
mentioning
confidence: 99%